Crime Rate Prediction and Prevention: Unleashing the Power of Deep Learning - Sangeetha, S.; Suganya, P.; Shanthini, S.; Murthy, G N Keshava; Sathya, R. (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
Around the world, crime is a serious issue that has an impact on many different communities. Given the rise in criminal behavior, it is essential to anticipate and stop crime before it happens. Using a chatbot to forecast crime rates and spread awareness using machine learning and deep learning is a creative way to tackle this issue. This project aims to create a chatbot that can forecast crime rates and increase public awareness of criminal activities. A sizable dataset of crime data, including details like location, time,and incident type, will be used to train the chatbot. Machine learning-based techniques will be used to preprocess the data and evaluate it for associations and trends. Using natural language processing techniques, the chatbot will converse with users and give them pertinent information about crime in their neighborhood. Chatbot is used to analyse the crime rate in a particular area. The chatbot will include a deep learning algorithm that can forecast crime rates using past crime data. As a result, law enforcement officials will be able to respond before a crime occurs. The chatbot will also offer security advice and tips on avoiding becoming a victim of crime. This ability of the study is to increase public awareness of crime and inspire individuals to take action to avoid it is one of its most significant benefits. By giving precise and up-to-date information on crime, the chatbot can help individuals make wise decisions regarding their safety and well-being. This chatbot can help people stay safe by using the power of machine learning and deep learning to deliver insightful information on crime trends.